Authoritarian Parenting and Bullying Behavior in Adolescents in Bali - Ni Putu Eka Febianingsih; Ni Made Sri Muryani (Babali Nursing Research, 2023)
Introduction: Bullying in adolescents harms all parties involved, the victims, perpetrators, bystanders present during the bullying event, and even the institution or schools. One important factor related to bullying among adolescents is parenting style. Methods: This study was a survey study involving the population of adolescents in Bali. A total of 783 eligible students recruited by consecutive sampling technique were participated in the study. Data was collected using a Google form questionnaire that was distributed through a Whatsapp group. Data were analyzed using the simple logistic regression analysis to discover the relationship between authoritarian parenting style and bullying behavior among adolescents. Results: Findings revealed that adolescents with authoritarian parenting styles posed a risk of being bullies by 3.87 higher than adolescents who received permissive and democratic parenting styles (95% CI:1.75 – 8.57) with a significance value of 0.001. Conclusion: This study showed that adolescents with authoritarian parenting have a 3.87 times higher risk of becoming bullies than adolescents who received permissive and democratic parenting.